‘It does not end with delivery?’ Pregnancy-associated thrombotic microangiopathy in the setting of postpartum preeclampsia/eclampsia – case report - I. Ivanko; Ž. Dika; I. Ćelap; V. Vukosav; P. Gaćina; J. Josipović (Blood Pressure)
Introduction Pregnancy-associated thrombotic microangiopathy (TMA) is potentially life-threatening disorder which refers to endothelial injury as the main culprit. Our case demonstrates true severity of pregnancy-associated TMA in postpartum period and diagnostic challenges in obtaining correct diagnosis.Case presentation The 32-year-old woman, with no previous record of gestational hypertension, underwent C-section in 30th week of 1st pregnancy due to preeclampsia. Postpartum period was complicated with TMA and continuous need for antihypertensive therapy. Due to suspicion of thrombotic thrombocytopenic purpura (TTP), plasmapheresis was started. After dismissing TTP diagnosis, plasmapheresis was continued while perusing other possible pregnancy-associated TMAs. After a period of stabilisation, anaemia and thrombocytopenia worsened with signs of renal impairment and the patient experienced hypertensive crisis, culminating with grand mal epileptic seizure. She was sedated and treated with intravenous antihypertensive therapy in the Intensive care unit setting. Anti-complement therapy was obtained due to high suspicion of atypical haemolytic uraemic syndrome (aHUS) but ultimately was not delivered due to the rapid improvement in clinical and laboratory findings. No high-risk polymorphism for aHUS were detected, rather multiple common risk variants for complement mediated TMA. The patient experienced full clinical recovery with minimal residual renal impairment.Conclusion this case is an example of pregnancy-associated TMA in the setting of preeclampsia in postpartum period which progressed to eclampsia due to the uncontrolled arterial hypertension. Upon vigorous blood pressure management, signs of TMA fully subsided.